Measuring capillary wave dynamics using differential dynamic microscopy. Issue 37 (29th August 2019) - Wang, Jing; McGorty, Ryan
Abstract : We report a novel extension of differential dynamic microscopy to measure the interfacial fluctuations in a colloid–polymer mixture. Abstract : The interface between two fluids is roughened by thermally excited capillary waves. By using colloid–polymer systems which exhibit liquid–gas phase separation, the time and length scales of capillary waves become accessible to optical microscopy methods. Here, we study such a system using bright-field optical microscopy combined with a novel extension of differential dynamic microscopy. With differential dynamic microscopy, we analyze images in order to determine the decay time of interfacial fluctuations spanning wavevectors from 0.1 to 1 μm −1 . We find capillary velocities on the order of 0.1 μm s −1 that depend on the sample composition in expected ways and that match values from the literature. This work demonstrates the first application of differential dynamic microscopy to the study of interfacial dynamics.